2018
DOI: 10.1097/prs.0000000000004361
|View full text |Cite
|
Sign up to set email alerts
|

Toradol following Breast Surgery: Is There an Increased Risk of Hematoma?

Abstract: Therapeutic, III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…It also pose great challenges to the clinicians due to unfavorable side effect profiles, abuse and tolerance ( 101 ). Ketorolac tromethamine (Toradol), a non-steroidal anti-inflammatory drug, is used frequently due to its success in relieving postoperative pain and reducing the need for narcotics ( 102 ). Recent study showed that the non-steroidal anti-inflammatory drugs (NSAIDs) are not associated with increased postoperative bleeding and have fewer complications than opioids ( 103 ).…”
Section: Measures To Prevent and Improve Postoperative Sleep Disturbamentioning
confidence: 99%
“…It also pose great challenges to the clinicians due to unfavorable side effect profiles, abuse and tolerance ( 101 ). Ketorolac tromethamine (Toradol), a non-steroidal anti-inflammatory drug, is used frequently due to its success in relieving postoperative pain and reducing the need for narcotics ( 102 ). Recent study showed that the non-steroidal anti-inflammatory drugs (NSAIDs) are not associated with increased postoperative bleeding and have fewer complications than opioids ( 103 ).…”
Section: Measures To Prevent and Improve Postoperative Sleep Disturbamentioning
confidence: 99%
“…A study of 168,990 patients undergoing nasal surgery (septoplasty, rhinoplasty, or inferior turbinate reduction) investigating the impact of NSAIDs on postoperative bleeding found no association between NSAIDs and increased postoperative complications including epistaxis, septal hematoma, emergency room visits, hospital readmission, and 30-day reoperation 39. Another study investigating the impact of ketorolac tromethamine (Toradol) on hematoma formation in breast surgery concluded that there was no statistically significant difference in hematoma formation due to ketorolac 40…”
Section: Discussionmentioning
confidence: 99%
“…Отечественные и зарубежные авторы сообщают о частом развитии гематом в послеоперационном периоде после различных хирургических вмешательств на молочной железе. По данным литературы, факторами риска развития гематом в послеоперационном периоде являются курение, ожирение, увеличение груди, лечение антикоагулянтами и пожилой возраст [20,21]. Как правило, ранние клинически значимые послеоперационные гематомы развиваются в течение первых 12-48 ч после операции, реже гематома появляется через несколько дней или недель после оперативного вмешательства.…”
Section: Discussionunclassified